Unveiling the interactive effect of green technology innovation, employment of disabilities and sustainable energy: A new insight into inclusive sustainability - Ragmoun, Wided; Alfalih, Abdulaziz (International Journal of Renewable Energy Development, 2025)
The interaction between green technology innovation, employment of disabilities, and sustainable energy is a critical area of research that addresses the emergent need for inclusive sustainability. Nowadays, the interaction between sustainable energy and green technology innovation is considered an essential field of research that has been widely discussed in previous studies. However, the role of employment, especially of people with disabilities, on this effect is still inexistent despite its relative importance for the achievement of sustainable development goals. By unveiling the interactive effect between these factors, strategies can be defined to reduce and limit the negative impact on the environment while promoting employment.  This study aims to fill this research gap by investigating the impact of green technology innovation and employment of disability on sustainable energy in 25 OECD countries from 1994 to 2020 using a dual methodological approach that integrates a parametric analysis: the panel vector autoregression (PVAR) model and a nonparametric assessment: the local linear dummy variable method (LLDV). The findings reveal (i) a significant positive correlation between the enforcement of green technology innovation and the increase in the employment rate of people with disabilities, (ii) a limited direct effect of green technology innovation on green energy consumption, and (iii) a positive impact of the interactive effect of employment of disabilities and green technology innovation, with a higher elasticity than that recorded by a separated effect. The outcomes address environmental challenges and promote social equity in the green economy. They also offer some critical recommendations for policymakers and researchers on sustainable energy.